Correlación entre el módulo resilente y el módulo dinámico para mezclas asfálticas tipo mdc-19 (2018)
The present work must like objective determine the existing correlation between the tests of resilient module and dynamic module, for a dense mixture in the heat of the moment with stony aggregate of maximum size of 19 mm (MDC-19) a conventional asphalt type AC a 60-70 and transit of design from 500 000 to 5 000 000 of equivalent axes of 8,2 tons in the design track during the period of design. The design of the mixture was realized with the Marshall methodology to determine the optimal one of theoretical asphalt, which the stability characteristics are fulfilled, flow, volumetric and dynamic properties of the mixture. Verified the mixture, one occurred to beginning to the execution of the tests for the determination of the resilient module and dynamic module to specific temperatures of test of 5, 25 and 40°C following the methodologies mentioned respectively.  The investigation concludes in the generation of a correlation that unifies the conditions of the test of resilient module and dynamic module to predict with a confidence level superior to 94% the value of rigidity for a mixture MDC-19, to different temperatures (Tmix) and different speeds from project design, this correlation has great importance to be used in the phases of the design or predesign of structures of flexible pavements.